(untitled) (diségno, 2019)
The great wonder of the word “drawing” lies in the ability to understand in its meanings a vast heterogeneity of phenomena and activities, belonging to the sphere of perception, knowledge, imagination and communication. Noble meanings, able to specialize when the word is accompanied by adjectives that specify the application feld. With Disegno digitale esplicito (Explicit digital drawing), Michele Calvano suggests to the readers to focus attention on a particular quality of drawing, which is prevalent in the digital meaning, consisting in the “explicitness” of the geometric-formal genesis: the synthetic and conceptual communication of the realization process of the drawing. This “narration” process takes place through indirect digital modeling tools, which are the modeling aids provided by the Visual Programming Language. These offer on the one hand the creative and expressive freedom characteristic of programming languages, and on the other hand the organizational and communicative capacity of fow charts. (read more)